Individual Counseling Miracle Question Technique to Overcome the Pessimistic Attitude for the Future of Client - Wieldy, Wieldy Caesar Nesta; Razzaq, Abdur; Fitri, Hartika Utami; Rachmad, Yoesoep Edhie; Utama, Ferdian (Grief and Trauma, 2024)
This thesis is entitled “Application of Individual Counseling with the Miracle Questions Technique to Overcome Pessimistic Attitudes for the Future (Case Study of Client X LPKA Palembang)”. This research aims to explore the Miracle Questions technique in individual counseling to overcome pessimistic attitudes towards the future. The client in this case study is an individual at LPKA Palembang designated as Client X. Through a series of counseling sessions, the Miracle Questions technique was used to help Client X formulate a more positive and optimistic vision about his future. This technique involves asking hypothetical questions about positive changes that might occur in Client X’s life, allowing him to imagine and plan concrete steps toward those changes. The research results show that the Miracle Questions technique can help Client X reduce pessimism and feel more empowered in facing the future. This thesis shows the potential of individual counseling and the Miracle Questions technique as an effective tool to help individuals overcome pessimistic attitudes towards the future.